Analisis Pengaruh Gender dan Faktor Sosial-Demografis terhadap Keputusan Menjadi Pekerja Digital di Indonesia - Putranto, FX Gugus Febri; Natalia, Christiayu; Pertiwi, Lita Gadis (Politeknik Statistika STIS, 2025)
The gender gap in participation as digital workers has persisted in recent years, even as the sector undergoes rapid growth and emerges as a major economic opportunity. This disparity is a critical concern, as women, who are often positioned within structurally disadvantaged groups, face a heightened risk of exclusion amid the ongoing digital transformation. This study analyzes opportunities to become digital workers, both in the formal and informal sectors, using microdata from the August 2023 National Labor Force Survey (Sakernas). An official statistics approach is applied through decent work indicators, and a multinomial logistic regression model is employed to examine gender-based disparities. The results indicate that women have significantly lower chances than men of being employed as digital worker, whether formal or informal. These findings underscore the need for affirmative policy interventions to improve women’s access to digital skills training, flexible work arrangements, and social protection within the digital economy.